STUDI PEMBUATAN RAINBOW CAKE MENGGUNAKAN PATI SAGU (Metroxylon sp.) LOKAL RIAU - Arnizam '; Usman Pato; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aim was to analyze the differences in the sensory assessment of the rainbow cake with the addition of 30% sago starch and 100% rainbow cake using wheat flour. This study used a Completely Randomized Design (CRD) with two treatments and eight replication thus obtained 16 experimental units. The treatments were TS1 (100% wheat flour, 0% sago starch) and TS2 (70% wheat flour, 30% sago starch). The parameters observed were descriptive test which includes assessing the attributes of tenderness, softness, cake flavor, colour brightness and sweetness. The results of this study indicated that rainbow cake with TS1 treatment (100% wheat flour, 0% sago starch) and rainbow cake with TS2 treatment (70% wheat flour, 30% sago starch) had no significant difference on tenderness, flavor cake, colour brightness and sweetness but significant effect softness of rainbow cake. Keyword : sago starch, wheat flour, rainbow cake, sensori